Landslides 2022
DOI: 10.5772/intechopen.101023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Landslide Risk in Ethiopia: Distributions, Causes, and Impacts

Abstract: The complex geological and geomorphological settings of Ethiopia, consisted of highland plateaus, escarpments, deeply dissected valleys, and flat lowlands, are results of multiple episodes of orogenesis, peneplanation, crustal up-doming, faulting, and emplacement of huge volumes of lava. The broad elevation contrast raging from about −125 m to 4550 m Above Mean Sea Level (AMSL) is an important factor in determining the climate regimes, vegetation types, and even populations’ lifestyles. In Ethiopia landslides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…4f, soil types of the study area are reclassified into five categories (acrisols, nit sols, fluvisols, litosols, and calcic xerosols) and the majority of the area is occupied by Acrisols (73%). Acrisols are among soil types commonly found in highland areas characterized by low levels of organic matter and are highly prone to landslide hazards because of delayed infiltration [26]. Thus, possible to conclude that soil type is among the contributing factors for landslide hazard that has been and will also continue to be a causative factor for landslide hazard susceptibility in the study area.…”
Section: Soil Typementioning
confidence: 87%
See 1 more Smart Citation
“…4f, soil types of the study area are reclassified into five categories (acrisols, nit sols, fluvisols, litosols, and calcic xerosols) and the majority of the area is occupied by Acrisols (73%). Acrisols are among soil types commonly found in highland areas characterized by low levels of organic matter and are highly prone to landslide hazards because of delayed infiltration [26]. Thus, possible to conclude that soil type is among the contributing factors for landslide hazard that has been and will also continue to be a causative factor for landslide hazard susceptibility in the study area.…”
Section: Soil Typementioning
confidence: 87%
“…Block B encompasses east and west Gojam and Gondar. Block C represents south and southwestern Ethiopia whereas; Block D constitutes the eastern part of the Main Ethiopian Rift [26].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia landslides mostly manifest as rock fall, earth slide, debris and mudflow especially in the steep and hilly areas of the highlands greater than 1,500 m altitude [7,8]. According to Meten et al [9], from 1960 to 2010 about 388 people are reported dead, 24 injured, and a great deal of agricultural lands, houses, and infrastructures were affected.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, landslides, mostly manifested as rock fall, earth slide, debris, and mudfow are among the major geohazards, especially in the steep and hilly areas of the highlands with greater than 1500 m altitude [7,8]. According to M. Meten et al [9], from 1960 to 2010, about 388 people are reported dead, 24 injured and a great deal of agricultural lands, houses, and infrastructures were afected.…”
Section: Introductionmentioning
confidence: 99%